2017
DOI: 10.3390/v9090248
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Alterations in Human Papillomavirus-Associated Cancers

Abstract: Approximately 15–20% of human cancers are caused by viruses, including human papillomaviruses (HPVs). Viruses are obligatory intracellular parasites and encode proteins that reprogram the regulatory networks governing host cellular signaling pathways that control recognition by the immune system, proliferation, differentiation, genomic integrity, and cell death. Given that key proteins in these regulatory networks are also subject to mutation in non-virally associated diseases and cancers, the study of oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 176 publications
(230 reference statements)
0
64
0
1
Order By: Relevance
“…The HPV genome is chromatinized in both its episomal and integrated forms. Viral proteins alter epigenetic regulation of host gene expression to promote viral genome expression (Soto et al 2017). Several chromatin modifiers and transcriptional regulators were recurrently mutated in HPV-positive OSCCs, including histone acetyltransferase EP300, lysine methyltransferases KMT2D and NSD1, the core histone HIST1H2AE, and transcription factors CASZ1, BBX, and TAF5.…”
Section: Discussionmentioning
confidence: 99%
“…The HPV genome is chromatinized in both its episomal and integrated forms. Viral proteins alter epigenetic regulation of host gene expression to promote viral genome expression (Soto et al 2017). Several chromatin modifiers and transcriptional regulators were recurrently mutated in HPV-positive OSCCs, including histone acetyltransferase EP300, lysine methyltransferases KMT2D and NSD1, the core histone HIST1H2AE, and transcription factors CASZ1, BBX, and TAF5.…”
Section: Discussionmentioning
confidence: 99%
“…These modifications lead to abnormal gene expression in HPVassociated carcinomas by activating oncogenes and transposable elements, which in turn leads to the loss of imprinting or to the inactivation of tumor suppressor genes. 56 Additionally, studies have detected amplification and/or overexpression of the proto-oncogene MYC, localized at 8q24.21, a recognized viral genome insertion site. 6,11,12 Our data revealed increase of MYC copy number in 65% of the tumors, supporting other authors who suggested, that infection may act promoting PeCa establishment by different mechanisms.…”
mentioning
confidence: 99%
“…It has also shown that in 85% of women with HSIL, IGFBP 2 loss expression occurs, which could has clinical utility for monitoring patients with a higher risk of CxCa progression [39]. Some epigenetic mechanisms have been described in CxCa, related to the effects of HPV on viral and host genome [40,41]. Some of them involve the components of the IGF system, such as IGF2 loss of imprinting, which can lead to some genes overexpression and overall chromatin instability [42] and E7 interaction with a group of lncRNA that modulate PI3K/Akt/mTOR and Wnt- catenin pathways in cervical carcinogenesis process [43].…”
Section: Contribution Of Insulin Resistance To Cxca Riskmentioning
confidence: 99%